2013
DOI: 10.3176/eco.2013.3.02
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the re-vegetation of abandoned extracted peatlands in Estonia: a synthesis from field and greenhouse studies

Abstract: Re-vegetation of extracted peatlands is a slow and sporadic process. The aim of our study was to clarify whether this process is affected by the distance from vegetated areas and propagules arrival or by the conditions for propagules germination and plant growth. Our analysis is based on three extracted peatlands in Estonia, abandoned 26-31 years ago. In all study areas vegetation was analysed on the gradient from a neighbouring vegetated area towards the central part of the peatland. In addition, peat blocks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 27 publications
3
11
0
Order By: Relevance
“…Stripping is not particularly laborious , and since it is also required to level surfaces, stripping should be applied for faster recovery of carpets of Sphagnum mosses. The results confirmed earlier findings from a greenhouse experiment (Triisberg et al 2013) that the germination of propagules and spontaneous revegetation of extracted peatlands is affected mainly by moisture conditions. The water-table depth had a significant effect (p=0.03, Table 2) on the cover of bryophytes, although this effect may be species-specific.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Stripping is not particularly laborious , and since it is also required to level surfaces, stripping should be applied for faster recovery of carpets of Sphagnum mosses. The results confirmed earlier findings from a greenhouse experiment (Triisberg et al 2013) that the germination of propagules and spontaneous revegetation of extracted peatlands is affected mainly by moisture conditions. The water-table depth had a significant effect (p=0.03, Table 2) on the cover of bryophytes, although this effect may be species-specific.…”
Section: Discussionsupporting
confidence: 93%
“…It has been shown that the time since the end of peat extraction has a positive effect on spontaneous re-vegetation of extracted peatlands (Triisberg et al 2013). There has been a remarkable establishment of Sphagnum cover for the third year of restoration compared to the scanty plant cover in abandoned extracted peatland (control site).…”
Section: Discussionmentioning
confidence: 98%
“…Grosvernier et al () found that peat organic content or total C content is positively correlated with Sphagnum growth. Triisberg et al () also established that the distribution pattern of Sphagnum communities on abandoned peatfields is connected with a low peat ash content.…”
Section: Discussionmentioning
confidence: 97%
“…Substrate properties (pH, moisture, peat organic content, and nutrient content) are essential for the formation and development of moss species composition and thus for the outcome of restoration activities. According to Triisberg et al (), the peat organic content is one of the main factors determining the vegetation structure on abandoned milled peatlands, well related to other relevant factors like pH, decomposition level, the content of K, Mg, and P (Paal et al ), and the thickness of residual peat (Triisberg et al ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, well-lighted conditions hindered development of this species in blueberry plantations and bare peat area in our experiments. D. polysetum has been recorded in a natural revegetation study in harvested peatlands, abandoned 26-31 years ago (Triisberg et al, 2013). However, the species appeared to a small degree.…”
Section: Abundance Of Vegetation Depending On Experimental Sitementioning
confidence: 99%